The Use of Content-Marketing in Complex Development of Non-Urbanized Territories in Russia - A. D. Zhukovskii (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with practical aspects of using content-marketing to improve social and economic appeal and complex development of non-urbanized territories in Russia. The author showed that the process of business climate development on territories with low population density is a whole complex of measures. In practice they are connected with target positioning of each region and spot lighting of its concrete benefits for potential partners and economically active people, who would like to swap their megalopolis for more placid life and realize themselves beyond big cities. It was shown that content-marketing can serve as a universal tool for resolving problems of regional development in Russia. It is based on approaches of step-by-step bringing the target audience to decisionmaking about buying goods, services or taking part in an investment project. In case of Russian regions it means a decision to invest in the region, set up highly-technological enterprises or business connected with agriculture. At the same time entrepreneurs could get an additional incentive for realizing their ideas in the form of state support with a broad range of tax privileges and subsidies and as maximum – availability of a preferential zone in the region, where state is interested in creating jobs and intensive development of a concrete territory. It was underlined that in Russia preferential zones are mainly arranged on non-urbanized territories far from big cities and agglomerations. The article provided examples of content-marketing functioning in promotion of existing highlytechnological enterprises and business-projects being developed now in every region of the country. The use of successful experience in developing regions was studied also on less successful territories, which require operative alterations in their positioning. A conclusion was drawn that high-quality positioning of the region is a secure investment in its development and a universal tool for sustainable development of non-urbanized territories in Russia.